Active control of noise and vibration - Hansen, Colin H., 1951- (CRC Press, Taylor & Francis Group, 2012)
Since the publication of the first edition, considerable progress has been made in the development and application of active noise control (ANC) systems, particularly in the propeller aircraft and automotive industries. Treating the active control of both sound and vibration in a unified way, this second edition of Active Control of Noise and Vibration continues to combine coverage of fundamental principles with the most recent theoretical and practical developments. What's New in This EditionRevised, expanded, and updated information in every chapterAdvances in feedforward control algorithms,